Determination of Chlorogenic Acid and Rutinum in Herba Artemisiae Scopariae with Multitemplate Molecularly Imprinted Polymers for Solid-phase Extraction with High-performance Liquid Chromatography. (2nd September 2017) - Tang, Weiyang; Ma, Wanwan; Row, Kyung Ho
ABSTRACT: Novel multitemplate molecularly imprinted polymers were prepared using mixtures of chlorogenic acid and rutinum as molecular templates, acrylamide as a functional monomer, divinylbenzene as the cross-linker, and 20:80 methanol:acetone as the porogen. The polymers were assessed for solid-phase extraction (SPE) for the purification of two compounds from Herba Artemisiae Scopariae . The synthesized molecularly imprinted polymers were identified by infrared spectroscopy and scanning electron microscopy. Systematic characterization of the functional monomer and porogens on the recognition properties of the molecularly imprinted polymers were carried out. Comparison with single-template molecularly imprinted polymers showed that the multitemplate molecular polymers exhibited higher selectivity and adsorption capacity for multiple analytes. The optimization of washing solvent as 1:9 acetone:water and the elution solvent as 9:1 acetonitrile:acetic acid provided a reliable analytical method with strong recognition toward multiple analytes in Herba Artemisiae Scopariae extracts with satisfactory recoveries of 89.6% for chlorogenic acid and 93.8% for rutinum. These results demonstrate that the multitemplate molecularly imprinted polymers coupled with SPE are effective for the selective purification of bioactive compounds in complex samples.